2021
DOI: 10.1128/iai.00644-20
|View full text |Cite
|
Sign up to set email alerts
|

Tryp-ing Up Metabolism: Role of Metabolic Adaptations in Kinetoplastid Disease Pathogenesis

Abstract: Today, more than a billion people – one-sixth of the world’s population – are suffering from neglected tropical diseases. Human African trypanosomiasis, Chagas disease, and leishmaniasis are neglected tropical diseases caused by protozoan parasites belonging to the genera Trypanosoma and Leishmania. About half a million people living in tropical and subtropical regions of the world are at risk of contracting one of these three infections. Kinetoplastids have complex life cycles with different morphologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Given the low parasite load during chronic T. cruzi infection, detected metabolites are most likely host-derived. Metabolic changes therefore reflect both direct parasite impacts on host metabolism, as well as host compensatory mechanisms and immunometabolism 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the low parasite load during chronic T. cruzi infection, detected metabolites are most likely host-derived. Metabolic changes therefore reflect both direct parasite impacts on host metabolism, as well as host compensatory mechanisms and immunometabolism 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Trypanosoma cruzi showed elevation of acylcarnitine C20:4 in the esophagus and small intestine during acute-stage infection [7], and likewise we saw elevated acylcarnitines in this study. This may reflect infection-induced alterations in energy metabolism during kinetoplastid infection [48]. Purines and pyrimidines are salvaged by Leishmania.…”
Section: Discussionmentioning
confidence: 99%
“…A handful number of drugs are available which are unfortunately associated with toxicity, difficulty in administration, cost or drug resistance. There is a need for novel drugs, and there has been many studies investigating different metabolic pathways in Leishmania that could eventually be exploited for drug development (reviewed in [ 1 4 ]).…”
Section: Introductionmentioning
confidence: 99%